RESEARCH OF COMPOSITES FEATURES BY SOLVING THE DIRECT AND INVERSE PROBLEMS OF THERMAL ELASTICITY - Povhorodnii, Volodymyr; Lelyushok, Oleh (Problems of Friction and Wear, 2023)
The article provides an analytical solution to the three-dimensional coupled problem of thermoelasticity for a composite whose structure and possible defects are given by trigonometric polynomials. Parameters of the temperature field arising as a result of defects in its structure are used in the diagnosis of defects in its structure. This is of great importance and practical value for non-destructive testing tasks. An expedient way of finding temperature values as a function of time and geometric coordinates is also the solution of inverse problems of thermoelasticity, i.e. determination of the temperature field based on the field of temperature stresses. The economy of this method lies in the fact that its application makes complex experimental studies of technical objects cheaper and eliminates the need to create computational and analytical methods that accompany these studies.